Pengaruh Pembelajaran Teams Games Tournaments Menggunakan Media Puzzle Pada Materi Organisasi Pergerakan Nasional Terhadap Hasil Belajar IPS Siswa Kelas VIII SMP Negeri 8 Binjai Tahun Pelajaran 2019-2020 - fakhruna una saif; Fathur Fathur Rahman (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2021)
Abstract: This study was conducted to see the effect of learning teams games tournaments using puzzles on the organizational material of the Indonesian independence movement on learning outcomes for class VIII students of SMP Negeri 8 Binjai in the 2019-2020 school year. This research is a quantitative study, where quantitative research emphasizes data processing in the form of numbers and in processing data in this study using the help of Microsoft Excel 2010. All class VIII in this school is defined as the research population consisting of 5 classes. The samples in this study were class VIII-1 and VIII-3 determined based on cluster random sampling. The experimental class is class VIII-1 and the control class is class VIII-3.This research data collection using a test instrument, the test is distributed to all samples with the same number and questions. Analysis of the data used in this study is the T test and N-Gain test. Before referring to the T-Test and N-Gain Test, the overall data must be homogeneous and of normality. So that the desired results are obtained on the t-test and N-Gain test. The final results in this study indicate that there is a significant effect between learning teams games tournaments using puzzle media on learning outcomes by obtaining results from T Count = 19.73 > T Table = 1.697 with a level of 0.05. Based on the results of the N-Gain test, it can be concluded that the application of learning teams games tournaments using puzzles is included in the category of effective and appropriate learning to be applied in social studies subjects for national movement organizations with the resulting score level of 75.89.The conclusion of this study is that learning teams games tournaments using puzzles has a significant influence on social studies learning outcomes for class VIII SMP Negeri 8 Binjai.Keywords: Teams games tournaments, Puzzle, Learning outcomes Hasil